IMPLEMENTATION OF THE DESIGNATION OF NICKEL MINING AREA IN KAWASI VILLAGE, ISLAND OF OBI - Rivaldo Jeverson Lemenz Totononu; Diana Darmayanti Putong; Janeman Jehezkiel Lanawaang; Lesza Leonardo Lombok (International Journal of Applied Science and Sustainable Development (IJASSD), 2025)
Sustainable development principles ensure current needs are met without compromising future generations' capabilities, integrating economic, socio-cultural, and environmental aspects for a balanced approach. Spatial planning, under Law Number 26 of 2007, defines regions based on administrative or functional aspects and areas for protection and cultivation. Mining activities in South Halmahera, including minerals, coal, oil, natural gas, and geothermal resources, contribute to regional economic growth while managing land use and environmental impacts. Specifically, mineral mining covers Bacan, Obi, Kasiruta, and Kayoa districts, particularly benefiting Obi's Kawasi Village under PT HARITA GROUP, generating jobs and attracting diverse investments. This study evaluates whether South Halmahera's Regional Regulation Number 20 of 2012 and PT HARITA GROUP's mining practices in Obi Islands adhere to sustainable development principles. By using normative legal method, the author finds that South Halmahera Regency Regional Regulation Number 20 of 2012 concerning Regional Spatial Planning contains the principles of sustainable development. From a juridical aspect, the designation of the nickel mining area is carried out by PT. Harita Group has been established in accordance with statutory regulations. However, there are indications that the mining carried out does not fully implement the principles of sustainable development. This is known from research conducted by WALHI North Maluku in 2023, namely the pollution of the waters of Weda Bay and Obi Island. This means that the mining process is carried out without paying attention to sustainable principles. This could be due to a lack of supervision by the relevant institutions. However, procedural supervision is not regulated in South Halmahera Regency Regional Regulation Number 20 of 2012 concerning Regional Spatial Planning.